9,9-Dibutyl-9H-fluorene-2-carbonitrile - Zhao, Dong-dong (International Union of Crystallography, 2012)
The fluorene fragment of the title compound, C(22)H(25)N, is essentially planar, with an r.m.s deviation of the five-membered ring of 0.005 (2) Å. The dihedral angle between this ring and the outer benzene rings are 1.5 (2) and 0.7 (2)° while that between the benzene rings is 2.1 (2)°. The cyano group makes an angle of 0.3 (2)° with the attached benzene ring.